2017
DOI: 10.1210/en.2017-00500
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin and Neurokinin B Signaling Network Underlies the Pubertal Increase in GnRH Release in Female Rhesus Monkeys

Abstract: Loss-of-function or inactivating mutations in the genes coding for kisspeptin and its receptor (KISS1R) or neurokinin B (NKB) and the NKB receptor (NK3R) in humans result in a delay in or the absence of puberty. However, precise mechanisms of kisspeptin and NKB signaling in the regulation of the pubertal increase in gonadotropin-releasing hormone (GnRH) release in primates are unknown. In this study, we conducted a series of experiments infusing agonists and antagonists of kisspeptin and NKB into the stalk-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…Earlier studies in rats have produced varied results showing that NKB can either stimulate or inhibit GnRH/LH secretion, often depending on species, sex and age. The present study clearly shows a stimulatory action of senktide/NKB to release GnRH which supports previous studies showing increased GnRH/LH release in prepubertal female rats sheep and rhesus monkeys, as well as in adult sheep and mice …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Earlier studies in rats have produced varied results showing that NKB can either stimulate or inhibit GnRH/LH secretion, often depending on species, sex and age. The present study clearly shows a stimulatory action of senktide/NKB to release GnRH which supports previous studies showing increased GnRH/LH release in prepubertal female rats sheep and rhesus monkeys, as well as in adult sheep and mice …”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the inability of senktide to stimulate Kp release in the present study could be the result of a species difference or to the low levels of oestradiol in late juvenile female rats. Interestingly, this previous study also showed that NKB and Kp take independent signalling paths to affect the release of GnRH in prepubertal female monkeys . Another report using tissue slices from adult male transgenic mice also indicated that NK3R activated GnRH release was Kp‐independent .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In PA female sheep, fetal T exposure reduces synaptic input to GnRH neurons [96], including diminished synaptic connections from hypothalamic AR-expressing kisspeptin/neurokinin B/dynorphin (KNDy) neurons [97] and diminished synaptic inter-connections between hypothalamic KNDy neurons accompanying lower post-synaptic expression for the neurokinin B receptor [97,98]. Since the kisspeptin and neurokinin B network plays a key role in neuronal stimulation for GnRH release in rhesus monkeys [99,100] and, together with dynorphin, is functionally implicated in regulating GnRH release in men [101], fetal T exposure may either enhance kisspeptin and neurokinin B stimulation of episodic GnRH release or impair dynorphin-mediated GnRH inhibition. A KNDy neuronal site for PCOS reproductive pathogenesis is consistent with therapeutic results obtained from neurokinin B NK3-receptor antagonist treatment of women with PCOS.…”
Section: Discussionmentioning
confidence: 99%